Endometriosis : A Rare Etiology for Small Bowel Obstruction - Sutradhar, Arpita; Ghatak, Supriyo; Gulati, Sumit; Roy, Ramdip; Basu, Amarnath; Basak, Arnab (Annals of Pathology and Laboratory Medicine, 2023)
Endometriosis affecting gastrointestinal tract has been reported in 3-37% of menstruating women. It is seen in the recto-sigmoid, caecum, small bowel and the appendix in decreasing frequency. Involvement of the ileum by endometriosis is quite rare ,1-7% cases have been documented..Endometriosis of ileal segment of gastrointestinal tract leading to intestinal obstruction ranges from 7% to 23%.We report a 40 year. old female who presented with complete intestinal obstruction ten days with history of recurrent subacute intestinal obstruction for one year. She was previously treated with empirical Antitubercular drug to which she did not respond. Now histology of the resected specimen showed endometriosis in muscular propria and submucosa , leading to fibrosis and stricture formation.